2021
DOI: 10.1038/s41467-021-22131-1
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclasts protect bone blood vessels against senescence through the angiogenin/plexin-B2 axis

Abstract: Synthetic glucocorticoids (GCs), one of the most effective treatments for chronic inflammatory and autoimmune conditions in children, have adverse effects on the growing skeleton. GCs inhibit angiogenesis in growing bone, but the underlying mechanisms remain unclear. Here, we show that GC treatment in young mice induces vascular endothelial cell senescence in metaphysis of long bone, and that inhibition of endothelial cell senescence improves GC-impaired bone angiogenesis with coupled osteogenesis. We identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 119 publications
3
61
0
Order By: Relevance
“…Meanwhile, the abundance of osteoclast progenitors (CD14 + ) was not altered as detected by flow cytometry (Fig EV2D and E). Knowing that bone vascularization is critical for bone health (Yang et al , 2020; Liu et al , 2021), bone tissue sections of CKO and WT mice were co‐stained with CD31, a specific vascular endothelial surface marker, and endomucin (Emcn), a specialized capillary subtype coupling angiogenesis and osteogenesis. Results showed that the abundance of CD31 hi Emcn hi vessels was similar between CKO and WT mice at 2 weeks, and profoundly reduced in 3‐month‐old CKO mice compared with WT mice (Fig EV2F and G).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the abundance of osteoclast progenitors (CD14 + ) was not altered as detected by flow cytometry (Fig EV2D and E). Knowing that bone vascularization is critical for bone health (Yang et al , 2020; Liu et al , 2021), bone tissue sections of CKO and WT mice were co‐stained with CD31, a specific vascular endothelial surface marker, and endomucin (Emcn), a specialized capillary subtype coupling angiogenesis and osteogenesis. Results showed that the abundance of CD31 hi Emcn hi vessels was similar between CKO and WT mice at 2 weeks, and profoundly reduced in 3‐month‐old CKO mice compared with WT mice (Fig EV2F and G).…”
Section: Resultsmentioning
confidence: 99%
“…Childhood asthma is a “bad child condition” that predicts pulmonary function and airflow limitation in early adulthood. First, the related decline in pulmonary function may begin in infancy or fetus and continue to childhood and adulthood [ 12 ]. According to newspaper reports, asthma is associated with persistent low pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…All sections were observed using an Olympus BX51 microscope. Quantitative histomorphometry analyses were performed as described previously (85) in a blinded fashion using OsteoMeasure Software (OsteoMetrics, Inc.). The sample area selected for calculation was a 1 mm 2 area within the metaphyseal trabecular bone.…”
Section: Methodsmentioning
confidence: 99%